2023
DOI: 10.1073/pnas.2301061120
|View full text |Cite
|
Sign up to set email alerts
|

Climate and health benefits of a transition from gas to electric cooking

Abstract: Household electrification is thought to be an important part of a carbon-neutral future and could also have additional benefits to adopting households such as improved air quality. However, the effectiveness of specific electrification policies in reducing total emissions and boosting household livelihoods remains a crucial open question in both developed and developing countries. We investigated a transition of more than 750,000 households from gas to electric cookstoves—one of the most popular residential el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Gas stoves are common globally and in U.S. homes. Emissions from gas and propane stove combustion degrade indoor air quality ( 3 , 10 , 40 , 56 , 57 ) and are associated with adverse health outcomes that include pediatric asthma and hospitalizations ( 23 – 25 , 52 , 58 , 59 ). We report updated field estimates of NO 2 emission rates for gas stoves and previously unreported emission rates of NO 2 from propane stoves.…”
Section: Discussionmentioning
confidence: 99%
“…Gas stoves are common globally and in U.S. homes. Emissions from gas and propane stove combustion degrade indoor air quality ( 3 , 10 , 40 , 56 , 57 ) and are associated with adverse health outcomes that include pediatric asthma and hospitalizations ( 23 – 25 , 52 , 58 , 59 ). We report updated field estimates of NO 2 emission rates for gas stoves and previously unreported emission rates of NO 2 from propane stoves.…”
Section: Discussionmentioning
confidence: 99%
“…Vanker et al found an association between fossil fuel use and degraded indoor air quality in homes, specifically higher levels of CO and benzene [22]. Nowadays, even though there has been a push towards electrification in homes to reduce exposure to carbon fuel-burning emissions and decrease the residential carbon footprint, often people are reluctant to upgrade their gas appliances to electric due to personal preferences, cost, and time constraints [23,24]. Increasing awareness of the potential for persistent low levels of CO in homes with a gas appliance could become an effective tool to raise awareness of the need for electrification of commonly used indoor appliances and to encourage society to adopt this change.…”
Section: Introductionmentioning
confidence: 99%